A New Viscoelastic Mechanics Model for the Creep Behaviour of Fibre Reinforced Asphalt Concrete (Fracture and Structural Integrity, 2018)
Based on the Burgers model, by adding a damper unit, this paper proposes a new viscoelastic model with five units and eight parameters to characterize the viscoelastic deformation of fibre reinforced asphalt concrete (FRAC). According to the creep tests of FRAC beams, this paper studies both the parameters in the model and the viscoelastic behaviour of FRAC with different fibre volume fraction and aspect ratio. In this model, this paper establishes the viscoelastic constitutive equation of asphalt concrete, which takes into account the impacts of fibre content characteristic parameter. Both the experimental study and theoretical analysis show that the new model has a high correlation with the results of creep experiment and plays a key role in describing the whole creep process of FRAC. The fibre content characteristic parameter can comprehensively reflect the effects of the fibre volume fraction and aspect ratio on the viscoelastic behaviour of FRAC. Within the range of this test, the optimum fibre volume fraction, fibre aspect ratio and fibre content characteristic parameter are 0.35%, 324 and 1.13, respectively.
Keywords: Fibre reinforced asphalt concrete; Viscoelastic model; Viscoelastic performance; Creep test; Fibre content characteristic parameter